Exploring Friendship Dissolution in Emerging Adulthood: The Role of Attachment Style - Muhammad Hafizh Kurnia; Yayah Khisbiyah (Universitas Muhammadiyah Surakarta, 2025)
Friendship is an interpersonal relationship built on voluntary feelings and sincerity among those involved, creating closeness between them (Fauziah, 2014). However, like other types of relationships, friendships can also come to an end, referred to as friendship dissolution. A meta-analysis of 227 studies involving 17.635 participants from adolescence to old age found a consistent patter of social circle reduction, including friendships, during emerging adulthood (Wrzus dkk., 2013). In 2024, an online research company, YouGov, surveyed 31.380 American adultls and found that 68% had experienced friendship dissolution. Among them, 58% ended friendship directly, 32% gradually, and 17% were unclear.Cultural factors may shape how friendships are perceived across regions. For instance, Hu & Tan (2013) found that in Asian countries such as China, friendships are seen as close and meaningful, often involving sharing personal matters and formed over a long period with loyalty, sincerity, and togetherness highly valued in collectivist cultures. In contrast, western countries like the United States tend to start friendships more quickly, emphasizing freedom and individuality. Emotional intimacy is often limited due to individualistic values that prioritize professionalism and personal boundaries, even in close relationship.One of the things that influencing the quality of friendships is attachment style. John Bowlby explained that attachment styles develop from the activation of attachment system when individuals face threats to safety, prompting them to seek proximity to attachment figures. This system can also be triggered by indirect threats, such as darkness, noise, or loneliness, as well as by emotional threats like separation or loss. As individuals grow, attachment figures expand beyond parents to include siblings, family members, coach, partners, even close friends (Mikulincer & Shaver, 2007).